Effectiveness of the automated writing evaluation program on improving undergraduates’ writing performance - Jingxin, Geng; Razali, Abu Bakar (Canadian Center of Science and Education, 2022)
Automated Writing Evaluation program (AWE) has gained increasing ground in ESL/EFL writing instruction because of its instructional features, such as the instant automated writing score system and the diagnostic corrective feedback in real-time for individual written drafts. However, there is little known about how the automated feedback provided by the AWE program can impact students’ writing performance in an authentic classroom and how to make the most of it to improve students’ writing performance effectively, especially for ESL/EFL undergraduate students. This paper attempts to offer an overview of the investigation of the effectiveness of automated feedback via a literature review. According to the inclusion and exclusion criteria, eleven articles published in the past five years were finally included for the analytical synthesis. The literature review matrix for the synthesis reveals the research gaps of the previous literature in the levels of the effectiveness of the automated feedback, including the lack of the design of delayed post-test, writing performance in terms of writing traits, and students’ writing strategies regarding the use of AWE program. The conclusion highlights the need for future research by bridging the gaps of exploring the long-term internalized impact of the embedded use of automated feedback and an advanced teaching method on improving both students’ overall writing performance and analytic writing scores.